2017
DOI: 10.1002/mde.2895
|View full text |Cite
|
Sign up to set email alerts
|

Managerial time constraints and young worker productivity: Natural experiments with NFL rookies

Abstract: The 2011 National Football League lockout and movement of the 2014 draft to a later date compressed the off‐seasons preceding the 2011 and 2014 seasons, exogenously tightening time constraints within which managers—head coaches and their staffs—engage in short‐run training of players. We exploit these natural experiments to investigate how this impacted the productivity of young workers (National Football League rookies). Results estimated for a sample of over 1,500 rookies support hypotheses emanating from an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…They also found that the survival of sports clubs is influenced by factors such as prior experience in top divisions, the number of titles won, and attendance. Allen and Curington (2018) explored the effects of exogenous off-season shortening in the National Football League (NFL) in 2011 and 2014. They found that players drafted during these periods performed worse than those who had the regular offseason, although this did not appear to significantly impact players' career durations.…”
Section: Survival Analysis In Sports Economicsmentioning
confidence: 99%
“…They also found that the survival of sports clubs is influenced by factors such as prior experience in top divisions, the number of titles won, and attendance. Allen and Curington (2018) explored the effects of exogenous off-season shortening in the National Football League (NFL) in 2011 and 2014. They found that players drafted during these periods performed worse than those who had the regular offseason, although this did not appear to significantly impact players' career durations.…”
Section: Survival Analysis In Sports Economicsmentioning
confidence: 99%
“…Analyzing each team over 14 seasons yields a balanced panel of 448 team‐year observations. As in Allen and Curington (2018), focusing on rookies enables observation of the cohorts of players who annually contribute most directly to the dynamic process by which new players enter the league as older players exit, with each team's and the league's immigrant‐native profile evolving as an observable artifact. Employer teams acquire first‐year players as part of an off‐season draft process common to all, ensuring that the employers participate in the same labor market process at the same time each year.…”
Section: Immigrants and Natives In The Nflmentioning
confidence: 99%
“…Analyzing each team over 14 seasons yields a balanced panel of 448 team-year observations. As in Allen and Curington (2018), focusing on rookies enables observation of the cohorts of players who annually contribute most directly to the dynamic process by which new players enter the league as older players exit, with each 11 The mechanism underlying this hypothesis illustrates, per Leiblein, Chen, and Rosen (2017), how uncertainty of a key resource ("asset") can interfere with the "emergence of competitive advantage" when organizations participate in strategic factor markets.…”
Section: Usementioning
confidence: 99%
“…This specific area of the literature generally focuses on two areas: career duration and career earnings. As it relates to career duration, existing studies examined various topics such as exit discrimination (e.g., Ducking et al, 2015), factors related to specific positions on the field of play (e.g., Salaga et al, 2020), league policies such as the amateur draft (e.g., Staw & Hoang, 1995), and a classification of players such as rookies (e.g., Allen & Curington, 2018). Results from this stream of literature highlight how both economic and social factors affect career length of players.…”
Section: Literature Reviewmentioning
confidence: 99%